PEMBUATAN GAME ACTION “I AM ...” MENGGUNAKAN GYROSCOPE DAN AUGMENTED REALITY PADA ANDROID - Ricky Yulianto; Jeanny Pragantha; Darius Andana Haris (Fakultas Teknologi Informasi Universitas Tarumanagara, 2020)
“I am” is an action game with Gyroscope to directing player according to smartphone’s orientation and Augmented Reality to scan markers to obtain skills and items. “I am” is made with Unity Game Engine, C# to program, Adobe Photoshop and Illustrator to design User Interface and buttons. “I am” tells the story of a witch named Rogana which lost his memories with severe wounds. Rogana was defeated by Karan who can leap through dimension as he wish to. Karan has the ambition to become the strongest magician. Rogana survived and tried to take revenge on Karan. Testing on this game done by blackbox, alpha testing and beta testing through a questionnaire conducted by 31 people. Test results show that the game I am has a unique gameplay with Gyroscope and Augmented Reality features